2009
DOI: 10.1590/s0102-76382009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco para insuficiência renal aguda no pós-operatório de revascularização do miocárdio

Abstract: ARF was a frequent and severe postoperative complication associated with higher mortality and longer ICU stay, which presented as risk factors: longer CPB and cross-clamp times, mechanical ventilation > 24h and hemodynamic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…The ischemic acute syndrome may be secondary to the formation of atherosclerotic plaques or thrombus development [23] and thus suggest greater likelihood of ischemic attacks in other organs and systems leading to hypoperfusion. This association was reported in other studies in patients who developed AKI [4,7].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The ischemic acute syndrome may be secondary to the formation of atherosclerotic plaques or thrombus development [23] and thus suggest greater likelihood of ischemic attacks in other organs and systems leading to hypoperfusion. This association was reported in other studies in patients who developed AKI [4,7].…”
Section: Discussionsupporting
confidence: 88%
“…Volkmann et al [20] demonstrated that AKI may be hidden in over 25% of patients who underwent CABG. Thus, the existence of a classification criterion to detect early kidney as well as a proposal to unify the classification/definition of AKI are essencial [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors also indicated the RF as a risk factor for prolonged ICU [28], and others only when it was an existing condition in the preoperative period [8,11,12]. Differences in values of RF risk indicators between different studies may be associated with the diagnosis itself.…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatmentioning
confidence: 99%